The Routledge handbook of gender and violence - Lombard, Nancy (Routledge international handbooks, 2018)
Acknowledgements -- Introduction -- Theoretical discussions of gender and violence -- Coercive control as a framework for responding to male partner abuse in the UK : opportunities and challenges / Evan Stark -- What's in a name? : the scottish government, feminism and the gendered framing of domestic abuse / Nancy Lombard and Nel Whiting -- On the limits of typologies : understanding young men's use of violence in intimate relationships / David Gadd and Mary-Louise Corr -- Male victims : control, coercion, and fear? / Emma Williamson, Karen Morgan and Marianne Hester -- Domestic violence in lesbian, gay, bisexual and/or transgender relationships / Becky Barnes and Catherine Donovan -- Specific forms, representations of, and responses to, gendered violence -- The implications of pornification : pornography, the mainstream and false equivalences / Karen Boyle -- Statutory response to sexual violence : where doubt is always considered reasonable / Deborah White and Lesley McMillan -- Stalking as a gender based violence / Katy Proctor -- Cyber-trolling as symbolic violence : deconstructing gendered abuse online / Karen Lumsden and Heather M. Morgan -- The relationship between disability and domestic abuse / Jenna P. Breckenridge -- Child contact as a weapon of control / Kirsteen Mackay -- Defining femicide / Karen Ingala-Smith -- "Lad culture" and sexual violence against students / Alison Phipps -- Violence against older women / Hannah Bows -- Female genital mutilation : a form of gender based violence / Judy Wasige and Ima Jackson -- Gender and trafficking of children and young people into, within and out of England / Patricia Hynes -- Prostitution and violence / Natasha Mulvihill -- Conducting research on gendered violence -- Lost in translation? comparative and international work on gender-related violence / Gigi Guizzo, Pam Alldred and Mireia Foradada-Villar -- Methodological challenges of working with police data / Maureen Taylor -- Researching gender based violence with minoritised communities in the UK / Khatidja Chantler -- "Guys! stop doing it!" : young women's adoption and rejection of safety advice when socializing in bars, pubs, clubs and implications for future campaigns / Oona Brooks -- "Thinking and doing" : children's and young people's understandings and experiences of intimate partner violence and abuse (IPVA) / Christine Barter and Nancy Lombard -- Making our feelings matter : using creative methods to re-assemble the rules on healthy relationships education in Wales / Libby, Georgia, Chloe, Courtney, Olivia and Rhiannon with Emma Renold